Effect of electromagnetic treatment on fatigue resistance of 2011 aluminum alloy - Mohin, M. A.; Toofanny, H.; Babutskyi, Anatolii; Lewis, A.; Xu, Yigeng (World Scientific Publishing, 2016)
Beneficial effects of the electromagnetic treatment on fatigue resistance were reported on several engineering alloys. These could be linked to the dislocation activity and the rearrangement of the crystal structure of the material under the electromagnetic field (EMF), resulting in delayed crack initiation. This paper presents an experimental study on the effect of pulsed electromagnetic treatment on the fatigue resistance of 2011 aluminum alloy. Circular cantilever specimens with loads at their ends were tested on rotating fatigue machine SM1090. Fatigue lives of treated and untreated specimens were analyzed and compared systematically. It has been found that the effect of the pulsed electromagnetic treatment on the fatigue resistance is dependent on the intensity of the pulsed EMF and the number of the treatment applied. Clear beneficial effect of the pulsed electromagnetic treatment on the fatigue resistance of the aluminum alloys has been observed, demonstrating a potential new technique to industries for fatigue life extension.
Keywords: Electromagnetic treatment; Fatigue resistance; Aluminium alloy